Autoregulation of Adenovirus Type 5 Early Gene Expression II. Effect of Temperature-Sensitive Early Mutations on Virus RNA Accumulation - Carter, T. H. (1978)
The kinetics of accumulation of early virus RNA in the cytoplasm of KB cells infected at 40.5°C by wild-type (WT) adenovirus type 5 and a temperature-sensitive “early” mutant, H5ts125 (ts125), were compared by hybridization of unlabeled RNA in solution to the (3)H-labeled l strand of Ad5 DNA HindIII restriction endonuclease fragment A. In the presence of 1-β-d-arabinofuranosylcytosine, A(l) RNA accumulated in WT-infected cells for 9 h and then decreased in concentration to 6% of the 9-h concentration by 18 h. In ts125-infected cells, A(l) RNA accumulated for 12 h and then remained at the same concentration for at least 6 h thereafter. The concentrations of virus RNA from the four early transcription regions of the genome were measured at 15 h in cells infected at 40.5°C in the presence of 1-β-d-arabinofuranosylcytosine by: (i) ts125 and WT; (ii) two other ts early mutants, ts107 and ts149; and (iii) a revertant of ts125. The revertant and ts149, a mutant from a different complementation group than ts125, both accumulated all early virus cytoplasmic RNA species in amounts similar to, or less than, WT. However, both ts125 and ts107, independently isolated mutations in the 72,000-molecular-weight (72K) DNA-binding protein gene, accumulated cytoplasmic early RNA in excess of that found in WT infection. This pattern of RNA accumulation with the mutants and WT virus was the same in the nuclei as in the cytoplasm at 40.5°C. At 32°C, however, the abundance of nuclear virus RNA from all four early regions was the same in cells infected by either ts125 or WT. Differences in the relative abundance of nuclear RNA from the four early regions were observed in cells infected at 40.5 and 32°C, but were not dependent upon the infecting virus genotype. These results are consistent with autoregulation of early gene expression by the 72K protein and support the hypothesis that the 72K protein either decreases the rate of early virus transcription or increases the rate of virus RNA degradation in the nucleus.